Taxation of Gratuitous Acquisition of the Ownership of Tangible Property and Property Rights in Polish and Lithuanian Tax Legislation Selected Problems - Babiarz, Stefan (Teisė, 2019)
[full article, abstract in English] The comparison of the inheritance tax legislation in Poland and Lithuania shows clearly that inheritance tax is a simple tax, with no special legal or financial complexity. Therefore, there are no serious issues concerning the assessment and/or payment of the tax. The assessment process and the amounts of the tax are taxpayer-friendly. It is worth noting solutions such as a 30% reduction in the taxable amount, no deduction of debt and charges, no complicated procedure for determining the taxable amount, respecting the double taxation avoidance principle, or the fact that no tax liability in respect of inheritance tax may re-arise. The case is not the same with the Polish Gift and Inheritance Tax Act. The only advantage of the Polish law, as compared to the Lithuanian law, is that the scope of taxable property is broader and, therefore, the higher, personal income tax would not apply to many types of the taxable property. The author expects this paper to be the first is a series of papers introducing Polish taxpayers, tax authorities and legislative bodies to legal solutions relating to the taxation of gratuitous acquisition of tangible property and property rights in other European countries. The Polish Gift and Inheritance Tax Act is a highly complicated piece of legislation. Its complexity causes tax disputes and does not encourage good relations between taxpayers and tax authorities. What is more, it is often the source of family conflicts.